2009
DOI: 10.1038/nsmb.1705
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori CagA inhibits PAR1-MARK family kinases by mimicking host substrates

Abstract: The CagA protein of Helicobacter pylori interacts with numerous cellular factors, and is associated with increased virulence and risk of gastric carcinoma. We present here the co-crystal structure of a subdomain of CagA with the human kinase PAR1b/MARK2, revealing that a CagA peptide mimics substrates of this kinase family, resembling eukaryotic protein kinase inhibitors. Mutagenesis of conserved residues central to this interaction renders CagA inactive as an inhibitor of MARK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
145
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(155 citation statements)
references
References 17 publications
(13 reference statements)
7
145
0
3
Order By: Relevance
“…Another remarkable characteristic of CagA N-terminal region is its flexibility, in particular the domain D1 (residues 1-300). Previously, most of the C-terminal region of CagA was found disordered, even when bound to the Par1b/MARK2 kinase (14). Here we found that domain D1, as well a number of loops of D2, D3, and D4, are highly flexible.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Another remarkable characteristic of CagA N-terminal region is its flexibility, in particular the domain D1 (residues 1-300). Previously, most of the C-terminal region of CagA was found disordered, even when bound to the Par1b/MARK2 kinase (14). Here we found that domain D1, as well a number of loops of D2, D3, and D4, are highly flexible.…”
Section: Discussionsupporting
confidence: 47%
“…In particular, specific sequences (named MKI) (Fig. 1A) located in the CagA C terminus inhibit Par1b/MARK2 kinase activity via mimicry of the enzyme's natural substrate (14). The inhibition of the PAR1b/MARK2 perturbs atypical PKC signaling, which results in disruption of tight junctions and loss of cell polarity (15).…”
mentioning
confidence: 99%
“…(ii) A circular dichroism spectrum of this domain shows one that is typical of a disordered protein (10). (iii) Residues 885-1005, comprising just the TPMs of CagA, resolved only 14 residues of CagA when crystallized in complex with MARK2 (28). (iv) Several intrinsic disorder prediction software programs suggest that regions of the C terminus are disordered.…”
Section: Table 1 Thermodynamic Parameters Of Binding Between Cagf Andmentioning
confidence: 99%
“…Ainsi, CagA se lie à la kinase MARK1 (MAP/microtubule affinity-regulating kinase 1) par l'intermédiaire de motifs (appelés MKI) situés dans la portion carboxy-terminale (Figure 1). Ces séquences miment le substrat naturel de la kinase et inhibent son activité, ce qui dérègle la polarité des cellules [4]. La partie carboxy-terminale de CagA peut être phosphorylée (CagA-P) par des kinases de la famille Src sur les tyrosines contenues dans des motifs EPIYA.…”
Section: Resultsunclassified